Philosophy of the Performing Arts - Davies, David -1937 (Chichester Blackwell, 2011)
This book provides an accessible yet sophisticated introduction to the significant philosophical issues concerning the performing arts.Presents the significant philosophical issues concerning the performing arts in an accessible style, assuming no prior knowledgeProvides a critical overview and a comprehensive framework for thinking about the performing artsExamines the assumption that classical music provides the best model for thinking about artistic performance across the performing artsExplores ways in which the 'classical paradigm' might be extended to other musical genres, to theatre, and to danceApplies the thinking on performing arts to the issue of 'performance art'
Keywords: Performing arts; Philosophy